Motoric performance variation from morning to evening: 80% intensity post-activation potentiation protocol impacts performance and its diurnal amplitude in basketball players - Eken, Özgür; Mainer-Pardos, Elena; Yagin, Fatma Hilal; Eken, Ismihan; Prieto-González, Pablo; Nobari, Hadi (Frontiers in Psychology, 2022)
Post-activation potentiation (PAP) can be defined as the acute enhancement in muscle performance after preload stimulation that occurs during strength exercises or warm-up protocols, and the contractile history of any muscle group can directly influence the presented performance. The purpose of this study was to compare the results of motoric performance tests carried out at two different times of the day using three different PAP protocols. Thirty-two male basketball players with at least two years of training experience and who competed at the national level were recruited for this study. After control and experimental-specific warm-up (SWU) sessions, participants completed a countermovement jump (CMJ) and seated medicine ball throw (SMBT). The SWU protocol was developed based on the athlete's typical warm-up routine. The experimental warm-ups included the same exercises as the SWU, with one set of bench presses for five repetitions at 80% (80% PAP) and one repetition at 100% of 1RM (100% PAP). Each of the protocols consists of 15 minutes. The SWU and experimental warm-up sessions were completed in a random, counterbalanced order, completed in a period of 3-weeks. According to the research findings, carrying out the protocols in the evening led to a larger improvement in SMBT compared to carrying out the protocols in the morning. Additionally, the SMBT results were statistically more significant in the group that received 80% PAP compared to the SWU, and the SMBT results were also higher in the group that received 100% PAP compared to the SWU. These results may provide more particular recommendations than previously thought to basketball coaches for the planning of basketball-specific PAP exercises prior to the start of training programs.